2017
DOI: 10.1101/gr.213694.116
|View full text |Cite
|
Sign up to set email alerts
|

The developmental proteome of Drosophila melanogaster

Abstract: Drosophila melanogaster is a widely used genetic model organism in developmental biology. While this model organism has been intensively studied at the RNA level, a comprehensive proteomic study covering the complete life cycle is still missing. Here, we apply label-free quantitative proteomics to explore proteome remodeling across Drosophila’s life cycle, resulting in 7952 proteins, and provide a high temporal-resolved embryogenesis proteome of 5458 proteins. Our proteome data enabled us to monitor isoform-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
174
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(207 citation statements)
references
References 59 publications
20
174
1
Order By: Relevance
“…This developmentally induced starvation precedes the extended pupal feeding arrest. The RNA profiles matched proteomic profiles performed on whole animals that confirmed the increased NimB5 expression at the onset of pupariation and higher levels as animals reach the end of the pupal stage and emerge [46].…”
Section: Interestingly Published Modencode Developmental and Tissuesupporting
confidence: 55%
“…This developmentally induced starvation precedes the extended pupal feeding arrest. The RNA profiles matched proteomic profiles performed on whole animals that confirmed the increased NimB5 expression at the onset of pupariation and higher levels as animals reach the end of the pupal stage and emerge [46].…”
Section: Interestingly Published Modencode Developmental and Tissuesupporting
confidence: 55%
“…PCC is a well‐established measure of correlation and ranges from + 1 (perfect correlation) to −1 (perfect but negative correlation), with 0 denoting the absence of a relationship (Adler and Parmryd, ). The PCC value ( r = 0.228) obtained in the present study revealed that the overall correlation between secretomic and transcriptomic data was weak, consistent with the familiar study on Drosophila melanogaster (Casas‐Vila et al ., ). The weak correlation between secretomic and transcriptomic data may be mainly attributed to the influence and regulation of transcription and translation by various factors that drastically affected the expression level of mRNAs and the accumulation of secreted proteins, underscoring the importance of proteomics to study invasion progression.…”
Section: Discussionmentioning
confidence: 97%
“…These include: the chitin-based cuticle that forms the animal's exoskeleton and lines the lumens of the foregut and hindgut [63][64][65]; noncuticular, chitin-based ECMs that line the lumens of the trachea, salivary glands, and midgut [64,66]; the eggshell that protects the developing embryo [67,68]; and the salivary glue that is produced by the larva to affix the pupa to a surface [69]. Defining the list of proteins that comprise these Drosophila-specific ECMs will provide a reference dataset for the arthropod clade and aid with the annotation of large proteomic datasets, including the developmental proteome of Drosophila [70]. Moreover, because insects can be both disease vectors and agricultural pests, these data could provide an important source of information to combat these threats to human welfare.…”
Section: Introductionmentioning
confidence: 99%